A green-nanocomposite film based on poly(vinyl alcohol)/ Eleusine coracana: structural, thermal, and morphological properties. Issue 3 (3rd April 2019) - Manikandan, K. M.; Yelilarasi, A.; Senthamaraikannan, P.; Saravanakumar, S. S.; Khan, Anish; Asiri, Abdullah M.
Abstract: Recently, polymer nanocomposites can offer to enhance the tremendous development of reinforcements and broaden their use in feasible applications. The polyvinyl alcohol (PVA) polymer based bio-nanocomposite film reinforced with different amount of Eleusine Coracana (EC) particles from 5 to 25 wt% were prepared by the solution cast. The bio-nanocomposite (PVA/EC) film was characterized by the X-ray diffraction (XRD), and Fourier transform infrared (FTIR). Thermo-gravimetric analysis (TGA) is used to estimate the thermal degradation of polymer bio-nanocomposites. From the Atomic Force Microscopy (AFM) analysis, the surface roughness of the (PVA/EC) film was analyzed.